PENGEMBANGAN APLIKASI PEMBELAJARAN TUNANETRA (APTUN) BERBASIS TEKNOLOGI ASISTIF UNTUK PENCARIAN KONTEN PEMBELAJARAN MAHASISWA TUNANETRA - Eko Perianto; Rianto Rianto; Taufik Agung Pranowo; Faiz Noormiyanto; Luqman Hidayat; Prahenusa Wahyu Ciptadi (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
Blind students have barriers and unique learning styles compared to other regular students. The fundamental difficulty is the absence of accessible content and tools that can help facilitate learning, including in the final project of blind students. The Blind Learning Application wants to accommodate the learning gaps experienced by blind students in the PGRI Yogyakarta University environment. Assistive technology in APTUN to find references that combines speech to text, Non Visual Desktop Access and text to speech that can be accessed online is one of the driving forces for fulfilling the needs and services of inclusive education at Universitas PGRI Yogyakarta through effective and efficient learning based on needs special education and services for students with visual impairments.